One Pulse Vector Control Inverter Control Design for Fast Train Traction Motor Torque Control - Mochammad Rusli; Wijono; Pramudita Pamungkas (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Current technology is increasingly developing, one of which is inverter control for high-speed train traction motor drives. Currently, the train driver is an AC electric motor. Inverters typically operate in the high-speed region. In this paper, it aims to drive the speed rotation of a 3-phase AC motor. The inverter is used to control the rotational speed of the motor, the vector control provides control of the speed and torque of the motor load for the 3 phase ac motor running at high speed. The vector control design is with the Arduino microcontroller program. The design of the inverter is in the form of a module that contains several components, namely IC drivers, resistors, mosfets, capacitors. The results of the PWM inverter were obtained in a waveform with a voltage of 4.72 volts, a frequency of 224.0 Hz and a duty cycle of 33.3%. The results of this study show the variation of the rotational speed of the motorcycle, the rotational speed of the motor with a value of 360 RPM the load torque response shows a value of 72.8 Nm, to the rotational speed of the motor of 960 RPM, the load torque response shows a value of 19.6 Nm. Based on the results of the inverter control research on motor torque control with the vector control method, the load torque response is able to follow the variation in the speed of rotation of the motor. The higher the rotational speed of the motorcycle, the lower the load torque respons.